The Role of Healthy Social Life, Food Security, and Nutrition in Shaping a Healthy Island: An Analysis Using Structural Equation Modeling - Palutturi, Sukri; Salahuddin, Nurul Syahriani; Birawida, Agus Bintara; Hidayanty, Healthy; Joko, Tri; S. Russeng, Syamsiar; Suriah, Suriah; Wahiduddin, Wahiduddin; Malek, Jalaluddin Abdul (Faculty of Public Health, Hasanuddin University, Makassar, 2023)
Several important factors are associated with establishing a healthy island including a healthy social life, food security, and nutrition but in-depth information related to these dimensions is limited. The relationship dimensions include addressing poverty, managing natural and social disasters, handling disabilities, food availability, and food security. Therefore, this study aimed to identify the best model for establishing a healthy island in South Sulawesi. The experiment was carried out on five islands located in three municipalities/regencies in South Sulawesi, namely Tanakeke Island in Takalar Regency, Barrang Caddi Island and Lummu-Lumu Island in Makassar Municipality, as well as Saugi Island and Sapuli Island in Pangkep Regency. The sample consisted of 196 households, while data were analyzed using multivariate analysis through structural equation model tests. The results showed that addressing poverty (t value = 13.77; R2 = 0.75), managing natural and social disasters (t value = 12.15; R2 = 0.61), as well as handling disabilities (t value = 12,53; R2 = 0.64) significantly affected healthy social life. Additionally, food availability (t value = 6.25; R2 = 0.66), and security (t value = 2.72; R2 = 0.85) played key roles in the relationship between food security and nutrition affecting a healthy island. The best indicator of a healthy social life variable was addressing poverty (t value = 13.77; R2 = 0.75). Meanwhile, the best indicator of food security and nutrition variables was food availability (t value = 6.25; R2 = 0.66).